2001
DOI: 10.1063/1.1410974
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond photoelectron imaging on pyrazine: Spectroscopy of 3s and 3p Rydberg states

Abstract: Two-color and one-color resonance enhanced multiphoton ionization photoelectron spectroscopies (REMPI–PES) have been applied to Rydberg states (n=3) of jet-cooled pyrazine. The 3s and 3p members of Rydberg series converging to the ground state (n−1) of the cation and the 3s member of a Rydberg series converging to an excited state of the cation (π−1) were observed. The photoelectron angular distributions (PADs) measured via the 3s(n−1) state drastically differed for the two-color and one-color REMPI experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
73
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 33 publications
8
73
3
Order By: Relevance
“…The photoelectron imaging method allowed identification of the intermediate states resonances as 3s(n -1 ) and 3p(n -1 ) Rydberg series. In contrast with the earlier studies of excited-state dynamics in pyrazine, 145 pyridazine interestingly showed no evidence of intersystem crossing dynamics (i.e., no triplet-state formation). Analysis of the PADs indicated mostly p-wave emission from the 3s state, whereas the 3p photoemission was comprised of a mixture of partial waves.…”
Section: Non-adiabatic Intramolecular Dynamicscontrasting
confidence: 99%
See 2 more Smart Citations
“…The photoelectron imaging method allowed identification of the intermediate states resonances as 3s(n -1 ) and 3p(n -1 ) Rydberg series. In contrast with the earlier studies of excited-state dynamics in pyrazine, 145 pyridazine interestingly showed no evidence of intersystem crossing dynamics (i.e., no triplet-state formation). Analysis of the PADs indicated mostly p-wave emission from the 3s state, whereas the 3p photoemission was comprised of a mixture of partial waves.…”
Section: Non-adiabatic Intramolecular Dynamicscontrasting
confidence: 99%
“…145 In that paper, the authors investigated in detail the spectroscopy and dynamics of the 3s and 3p Rydberg states involved in their previous two-probe photon ionization studies of the pyrazine S 1 state. 135 Through variation of the pump laser wavelength from 401 to 330 nm, series of singlet 3s(π -1 ), triplet 3s(n -1 ), and triplet 3pA(n -1 ) Rydberg states with sub-ps lifetimes were observed.…”
Section: Non-adiabatic Intramolecular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…28,64,65 After exciting pyrazine to the zero vibrational level in S 1 , we observed two-photon ionization from the S 1 and T 1 states using the 400 nm probe pulse, in which ionization was enhanced by accidental resonance with the Rydberg states. 64 The photoelectron signal intensities of S 1 and T 1 in Figure 10b exhibit respectively a gradual decay and growth as a function of time, in which characteristic spikes due to A(t) appeared (The S 1 state is probed via both 3s and 3p Rydberg states, 54,57 which exhibit opposite sign of the rotational coherence spikes). Similar signatures of A(t) is also seen in the photoelectron angular anisotropies (represented by ¢ 20 /¢ 00 in this case) in Figure 10c.…”
Section: Restoration Of Sharp Photoelectron Angular Distribution Frommentioning
confidence: 99%
“…The three peaks in the energy range of 1.52.7 eV are of the 3s, 3p z , and 3p y Rydberg states. 54,57 The distribution in the 02 eV range is due to photodissociation from higher valence states excited with 5½, so that the photoelectron kinetic energy diminishes rapidly as the vibrational wave packet moves away from the Franck Condon region. Let us examine the dynamics in comparison with the internal conversion in pyrazine.…”
mentioning
confidence: 99%